Integrasi Nilai-nilai Pancasila dalam Pengembangan Hard Skills dan Soft Skills Siswa di SDN Jetaksari 01 Sayung Demak dalam Menghadapi Tantangan Pendidikan Abad 21 - Adi Wahyu Pratama; Rida Fironika Kusumadewi (STKIP Subang, 2025)
This study aims to examine the integration of Pancasila values in developing students’ hard and soft skills at SDN Jetaksari 01 Sayung Demak in response to the challenges of 21st-century education. The 21st century demands that students possess critical thinking skills, digital literacy, collaboration abilities, and strong character to adapt to a rapidly changing world. Pancasila, as Indonesia’s national ideology and foundational philosophy, holds great potential as a basis for shaping students’ character and competencies. This research employs a literature review method based on the perspectives of Ali (2010) and Zed (2004), using a descriptive-qualitative approach to analyze relevant literature and document best practices from the school. The findings reveal that hard skills are strengthened through contextual and technology-based learning infused with Pancasila values, while soft skills are cultivated through daily routines, teacher role modeling, and extracurricular activities that promote values such as cooperation, responsibility, and empathy. Thus, integrating Pancasila values not only enhances students’ character but also supports the holistic development of 21st-century competencies. The study implies the importance of value-based education in primary schools to produce academically competent and morally grounded future generations. Recommendations are made for educators and policymakers to consistently incorporate Pancasila values as an integral part of both the curriculum and school culture.